When viral infections meet the anti-MDA5 antibody-positive dermatomyositis - Liu, Shuzi; Zhao, Zheng; Li, Yabin; Tan, Yao; Tian, Huabin; Xie, Fei (Frontiers in Immunology, 2026)
Anti-melanoma differentiation-related gene 5 (MDA5) antibody-positive dermatomyositis (anti-MDA5+ DM) is recognized as a distinct subtype of dermatomyositis, characterized by its frequent association with interstitial lung disease (ILD), particularly rapidly progressive ILD (RP-ILD), which is associated with a poor prognosis and high mortality. MDA5 functions as a cytoplasmic sensor for viral double-stranded RNA. The expression level of anti-MDA5 antibodies is positively correlated with disease severity. Notably, anti-MDA5 antibodies have been detected in patients infected with SARS-CoV-2. While the mechanisms underlying the generation of anti-MDA5 antibodies and their pathogenic role remain incompletely understood, accumulating data support the hypothesis that viral infections may trigger the production of these antibodies. This review provides a comprehensive analysis of the interplay between anti-MDA5 antibodies and viral infections in patients with anti-MDA5+ dermatomyositis (DM), with a focus on the potential mechanisms by which viral infections induce autoantibody formation.